CHI '14 Extended Abstracts on Human Factors in Computing Systems 2014
DOI: 10.1145/2559206.2581246
|View full text |Cite
|
Sign up to set email alerts
|

Using personalized radio to enhance local music discovery

Abstract: We explore the use of personalized radio to facilitate the discovery of music created by local artists. We describe a system called MegsRadio.fm that produces a customizable stream of music by both local and wellknown (non-local) artists based on seed artists, tags, venues and/or location. We hypothesize that the more popular artists provide context for introducing new music by more obscure local artists. We also suggest that both the easy-to-use and serendipitous nature of the radio model are advantageous whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…To date, the social computing community has examined online listening activity as source of information and recommendations for music (Bu et al 2010;Zheleva et al 2010;Farrahi et al 2014;Turnbull et al 2014). However, computational tools and online outlets such as social media can make further contributions toward understanding human behavior related to musical consumption and help to elaborate user-centric music retrieval systems by analyzing personal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the social computing community has examined online listening activity as source of information and recommendations for music (Bu et al 2010;Zheleva et al 2010;Farrahi et al 2014;Turnbull et al 2014). However, computational tools and online outlets such as social media can make further contributions toward understanding human behavior related to musical consumption and help to elaborate user-centric music retrieval systems by analyzing personal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Odom and Duel have contributed the OLO radio design artifact that allows people to explore and (re-)experience the music that they have listened to over the course of their lives [42]. Turnbull et al have found that personalized radio can help to stimulate the discovery of local music and local musical events [55]. Casagranda et al have proposed Hybrid Content Radio (HCR), which combines linear radio with OTT delivery of personalized audio content [7].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Latent Markov Embedding: Latent Markov Embedding (LME) [10,11,13,58,63] was recently proposed to tractably learn trajectories through a Markov chain whose states are projected user trajectories into Euclidean space. However, even with parallel optimizations [11] the method does not yet scaled beyond hundreds of thousands of users and items (as shown in Section 4.3).…”
Section: Related Workmentioning
confidence: 99%